Social Media and Public Sphere Jawa Tengah Province: Case Study @humasjateng - Mohamad Sukarno; Sakir (Universitas Pancasakti Tegal, 2024)
This study aims to find out and analyze the role of the Central Java Government as a public media sphere of society through social media accounts on Twitter by focusing on the intensity of interaction between user’s accounts. The research method used is qualitative. In terms of data analysis, the author uses Nvivo 12 Plus software for the process of interpretation and presentation of data. The results showed that the interaction of Twitter accounts @humasjateng decreased monthly due to the government's focus on handling the COVID-19 pandemic. In addition, the interaction built by the Central Java Government with users are quite intense and interactive.